AB0059 Effect of anti-tnf alpha treatment on serum levels of light (tnfsf14), cathepsin k, dkk-1 and sclerostin in ankylosing spondylitis: the osteoclast/osteoblast function balance and its relation to disease activity. (23rd January 2014) - Cauli, A.; Dessole, G.; Porru, G.; Piga, M.; Vacca, A.; Ibba, V.; Garau, P.; Mathieu, A.
Abstract : Background: Ankylosing Spondylitis (AS) is characterized by erosions and new bone formation wich resulting in classical syndesmophytes. These processes appear to be influenced by the fine balance of mediators involved in osteoclast activation, such as LIGHT (TNFSF14) protein and cathepsin K, and inhibition of osteoblastogenesis influenced by DKK-1 and sclerostin, although data available is still controversial. Objectives: To investigate in AS the serum levels of mediators involved in bone homeostasis, their relation to disease activity/disease severity and the modifications induced by anti-TNF-α treatment. Methods: 63 patients with AS have been consecutively recruited as well as 19 healthy controls (HC). 15 patients underwent anti-TNF-α treatment (Adalimumab), and were evaluated at baseline (w0) and 12 weeks after treatment (w12). Serum levels of DKK-1, sclerostin, cathepsin K and LIGHT were measured by ELISA assay (Biomedica, R&D System) and correlated with clinical scores (BASMI, BASFI e BASDAI), inflammatory markers (ESR and CRP) and disease duration. Data were expressed as mean ± SD. Differences among groups and statistical correlation have been analyzed according to data distribution by means of paired t-test, unpaired t-test with Welch's correction and Spearman's test. Results: Mediators of osteoclast activation were increased in AS patients compared to HC: LIGHT (115.1 pg/mL ± 74.8 vs 75.8 pg/mL ± 49.2; p=0.009), cathepsin-k (21 pmol/L ± 35.9 vs 9.6 pmol/L ± 5.8; p= 0.03), as well as mediators involved in osteoblast function: DKK-1 (36.4 pmol/L ± 18.8 vs 23.5 pmol/L± 17.6; p= 0.009), sclerostin (36.4 pmol/L ± 21.8 vs 25.1 pmol/L ±9.1; p= 0.001). The increase of these mediators resulted unrelated to disease activity, as evidenced by the lack of correlation of DKK-1, sclerostin, LIGHT and cathepsin-K with clinical scores and with disease duration; only LIGHT showed to correlate with ESR (p=0, 01; r=0, 4). It is also noteworthy the little modulation induced on these mediators by TNF-α antagonists, regardless the good clinical response according to EULAR criteria: DKK-1, LIGHT and cathepsin-k, w0 vs w12 p= ns, while increased sclerostin levels were observed at w12 compared with baseline (p=0.03). Conclusions: AS patients showed an increased bone metabolism, characterized by an increase of both mediators responsible of osteoclast and osteoblast function. This increased bone turn-over appear not linked to the inflammatory process and to disease activity, as perceived by the patient. Furthermore it appear to be independent to TNF-α related mechanisms, as recently suggested by radiological progression in patients with disease in clinical remission following anti-TNF-α treatment. Disclosure of Interest: None Declared